2nd IMU Conference on Medical education (Razi Medical Journal, 2025)
The central theme of ICME 2025 is “Advancing Excellence and Innovation in Medical Education Across Diverse Contexts.” The conference aims to provide a dynamic platform for dialogue, knowledge exchange, and collaboration, with a focus on curriculum development, faculty advancement, educational leadership, and transformative learning strategies.By convening distinguished voices from across the region and beyond, ICME 2025 seeks to inspire new perspectives on the future of medical education, strengthen institutional capacities, and promote academic excellence. The program will feature keynote speeches, panel discussions, and interactive sessions designed to foster meaningful engagement and actionable outcomes.